Cytochrome b Drug Resistance Mutation Decreases Babesia Fitness in the Tick Stages But Not the Mammalian Erythrocytic Cycle. (17th June 2021) - Chiu, Joy E; Renard, Isaline; George, Santosh; Pal, Anasuya C; Alday, P Holland; Narasimhan, Sukanya; Riscoe, Michael K; Doggett, J Stone; Ben Mamoun, Choukri
Abstract: Human babesiosis is an emerging tick-borne malaria-like illness caused by Babesia parasites following their development in erythrocytes. Here, we show that a mutation in the Babesia microti mitochondrial cytochrome b (Cytb) that confers resistance to the antibabesial drug ELQ-502 decreases parasite fitness in the arthropod vector. Interestingly, whereas the mutant allele does not affect B. microti fitness during the mammalian blood phase of the parasite life cycle and is genetically stable as parasite burden increases, ELQ-502–resistant mutant parasites developing in the tick vector are genetically unstable with a high rate of the wild-type allele emerging during the nymphal stage. Furthermore, we show that B. microti parasites with this mutation are transmitted from the tick to the host, raising the possibility that the frequency of Cytb resistance mutations may be decreased by passage through the tick vector, but could persist in the environment if present when ticks feed. Abstract : Human babesiosis is an emerging tick-borne disease caused by Babesia parasites. We show that a mutation that confers resistance to the antibabesial drug ELQ-502 decreases parasite fitness in the tick but does not affect its transmission to the mammalian host.